2021
DOI: 10.1055/a-1401-0215
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging of Bone Sarcomas and Soft-Tissue Sarcomas

Abstract: Background In the diagnosis of bone and soft-tissue sarcomas, the continuous advancement of various imaging modalities has improved the detection of small lesions, surgical planning, assessment of chemotherapeutic effects, and, importantly, guidance for surgery or biopsy. Method This review was composed based on a PubMed literature search for the terms “bone sarcoma,” “bone cancer” and “soft tissue sarcoma,” “imaging,” “magnetic resonance imaging”, “computed tomography”, “ultrasound”, “radiography”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Whereas prostatic metastases are typically osteosclerotic or osteoblastic in appearance on plain film radiography, PBL and the sarcomas predominantly exhibit an osteolytic pattern with soft tissue extension (34)(35)(36). Moreover, PBL and Ewing Sarcoma are known to cause periosteal reactions (35,36). However, prostatic bony metastases were found in one study to present as osteolytic themselves 16.4% of the time (37).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Whereas prostatic metastases are typically osteosclerotic or osteoblastic in appearance on plain film radiography, PBL and the sarcomas predominantly exhibit an osteolytic pattern with soft tissue extension (34)(35)(36). Moreover, PBL and Ewing Sarcoma are known to cause periosteal reactions (35,36). However, prostatic bony metastases were found in one study to present as osteolytic themselves 16.4% of the time (37).…”
Section: Discussionmentioning
confidence: 96%
“…Although we were unable to use MRI, it is a more suitable imaging modality for this purpose, with characteristic findings for PF including homogenous T1-hypointense signal abnormality at the site of fracture due, in part, to the tumor itself and potentially, in part, to edema and bleeding at the site (33). Whereas prostatic metastases are typically osteosclerotic or osteoblastic in appearance on plain film radiography, PBL and the sarcomas predominantly exhibit an osteolytic pattern with soft tissue extension (34)(35)(36). Moreover, PBL and Ewing Sarcoma are known to cause periosteal reactions (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…We considered it difficult to differentiate between primary sarcoma, carcinosarcoma, and carcinoma of the gallbladder; therefore, we searched the literature and listed the main differences between the most common tumors of the gallbladder in Table 3 [25–29] . Recently, studies have shown that positron emission computed tomography scanning is useful in differentiating malignant from benign diseases when using various radiopharmaceutical agents to improve the detection and characterization of the pathophysiology of the disease [30] . The fusion of positron emission computed tomography-acquired images with CT scans or MRI has significantly improved the overall diagnostic accuracy for sarcoma [31] .…”
Section: Discussionmentioning
confidence: 99%
“…With the wide use of 3D models with CT data in clinics, their limitations have been unveiled. The major limitation lies in their poor ability to distinguish the soft tissue part of the tumor from adjacent normal structures 14,15 . Poorly defined margins lead to inaccurate models which in turn results in misjudgments of the surgeons, increasing the risk of positive surgical margins.…”
Section: Introductionmentioning
confidence: 99%
“…The major limitation lies in their poor ability to distinguish the soft tissue part of the tumor from adjacent normal structures. 14,15 Poorly defined margins lead to inaccurate models which in turn results in misjudgments of the surgeons, increasing the risk of positive surgical margins. MRI, on the other hand, is a very handy tool in clinics in assessing soft tissue sarcoma margins.…”
mentioning
confidence: 99%